Small Distance Codes For Header Error Detection In Atm Networks - Antonio, Tony (JIK: Jurnal Ilmu Komputer, 2007)
On transmission links with relatively low bit error rates, error detection codes that have been widely used have dminÃ‚Â = 3. These codes may be unneccesarily powerful for fibre links because they require an excessive number of redundant parity check bits. For the purpose of error detection in ATM networks using optical fibre links, some high-rate, small distance codes with dmin = 2 may be appropiate. These codes, called Small Distance Codes, can be used to detect all single-error patterns and a large fraction of double errors and other patterns. This paper describes the application of small distance codes for error detection in the ATM cell header. Performances analysis are given and compared to the 8-bit CRC recommended by ITU-T. Three alternatives are examined and analysed. The results are displayed and compared to the standard 8-bit CRC and to 10-bit CRC for ATM network as well.Keywords: Small Distance Codes, Header Error, ATM Networks